Competencies and deficiencies in arithmetic skills of college freshmen students (1973-1974) in the Zamboanga State College their administrative and curricular implications - Fernandez, Efren G. 1921- ([Quezon City s.n.], 1974)
The subjects of the study--171 college freshmen enrolled in different courses were administered the revised form of Factor III (Numerical Reasoning) of the Standardized Multiple Aptitude Tests and the Basic Skills in Arithmetic Test. They showed competence in the multiplication, subtraction, and addition of whole numbers but are deficient in the division of whole numbers, and in the addition, subtraction, and multiplication of fractions including the subtraction and multiplication of decimal fractions.
Thesis (M.Ed.)--University of the Philippines.
Keywords: Zamboanga State College -- Students; Mathematical ability